Wideband and wide stopband superconducting bandpass filter using asymmetric stepped‐impedance resonators connected to open stub. Issue 7 (6th March 2020) - Luo, Chenjie; Wei, Bin; Wang, Xiang; Lu, Xinxiang; Cao, Bisong; Guo, Xubo; Jiang, Linan
Abstract: A wideband wide stopband filter is designed using asymmetric stepped‐impedance resonators (ASIRs) connected to a large open stub. The capacitive open stub and the parallel‐coupled microstrip line are used to achieve the strong couplings for large fractional bandwidth (FBW). For a wide‐stopband performance, the proposed filter uses ASIRs to improve the high‐order spurious resonant frequency. The first and last resonators of the proposed filter are further optimized to suppress the spurious resonant frequency caused by open stub. The final filter has a 70% FBW centered at 4.87 GHz with 20‐dB‐rejection stopband up to 15.78 GHz (approximately 3.24 f 0 ). The measured insertion loss is less than 0.15 dB and the return loss is better than 17 dB.